(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the linguistic foundations of the corpus of shevas and the principles of compiling a database of the corpus of Uzbek dialects. Information on the stages of compiling a corpus of data, the structure and size of the data warehouse is given. At the same time, it is thought what should be the emphasis on the formation of the database, what technical and linguistic work should be carried out in case of launching the dialectal corpus.